2011
DOI: 10.1037/a0023268
|View full text |Cite
|
Sign up to set email alerts
|

The reciprocal relationship between physical activity and depression in older European adults: A prospective cross-lagged panel design using SHARE data.

Abstract: Regular physical activity may be a valuable tool in the prevention of future depressive symptoms in older adults, and depressive symptoms may also prevent older adults from engaging in regular physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
130
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(149 citation statements)
references
References 50 publications
14
130
2
3
Order By: Relevance
“…These mechanisms seem plausible given that life dissatisfaction and negative emotions are more 13 frequently reported in adults with visual impairments than in adults without visual impairments (Fenwick et al, 2012;Senra et al, 2015). Because the relationship between PA and depressive symptoms is complex and reciprocal in nature (Lindwall, Larsman, & Hagger, 2011), we cannot exclude the possibility that depression symptoms led to lower levels of PA.…”
Section: Physical Activity and Depression Symptomsmentioning
confidence: 95%
See 2 more Smart Citations
“…These mechanisms seem plausible given that life dissatisfaction and negative emotions are more 13 frequently reported in adults with visual impairments than in adults without visual impairments (Fenwick et al, 2012;Senra et al, 2015). Because the relationship between PA and depressive symptoms is complex and reciprocal in nature (Lindwall, Larsman, & Hagger, 2011), we cannot exclude the possibility that depression symptoms led to lower levels of PA.…”
Section: Physical Activity and Depression Symptomsmentioning
confidence: 95%
“…It seems reasonable to adjust for baseline differences in HADS-D scores given that depression symptoms may influence PA and depression in the future (Lindwall et al, 2011). However, when there is considerable measurement error of the outcome, adjustment for baseline measures might result in inflated associations (Glymore, Weuve, Berkman, Kawachi, & Robins 2005).…”
Section: Physical Activity and Depression Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low SWL may lead to greater depressive symptoms, which are associated with feelings of lethargy and more sedentary time (Elliot, Kennedy, Morgan, Anderson, & Morris, 2012). Previous research on older adults and adolescents has also indicated bidirectional pathways between depressive symptoms and sedentary behavior (operationalized as a combination of frequency of sedentary behavior and low levels of physical activity; Lindwall, Larsman, & Hagger, 2011;Teychenne & York, 2013). Experimental research is needed to draw more precise conclusions related to the causal sequence linking sedentary behavior and SWL.…”
mentioning
confidence: 99%
“…They revealed that regular physical activity may be a valuable tool in the prevention of future depressive symptoms in older adults, and depressive symptoms may also prevent older adults from engaging in regular physical activity [29].…”
Section: Discussionmentioning
confidence: 99%